A world of endless promise manifesto of fragility - Bardaouil, Sam; Fellrath, Till; Bertolotti, Isabelle; Tachon, Franny (Silvana Editoriale, 2023)
The 16th Lyon Biennale: manifesto of fragility positions fragility at the heart of a generative form of resistance that is emboldened by the past, responsive to the present and primed for the future. Conceived as a collective statement, authored through word, image, sound and movement, it calls on a community of resilient voices to draft a manifesto for a world that is blamelessly fragile. The Biennale is structured around three distinct yet inter-connected layers, where fragility and resistance are explored through the lens of the individual, the city, and the world respectively. A World of Endless Promise assembles a host of creative practices by 88 artists from 39 countries that are spread across twelve locations spanning several centuries of Lyon’s rich history. Whether through the issues they tackle, or the materials they use, these artists’ diverse approaches represent varied understandings of our current state of global uncertainty and have the potential to inform our thinking about generative paths of resistance. In recognizing that artists, past and present, are often among the most vulnerable voices in our societies, the exhibition also brings together works of art and objects spanning millennia that bare their scars and deformities, share forgotten accounts of turmoil, and draw attention to the indelible traces of time. And it is exactly there, at the heart of their fragility, that the promise of a truly changed world begins
Colophon: This catalogue is published in conjunction with the exhibition "manifesto of fragility: A world of endless promise", 14 September - 31 December 2022
Keywords: Biennale d'art contemporain -- 16. -- 2022 -- Lyon; Art, Modern / 21st century / Exhibitions; Art / 21e siècle / Expositions; Art, Modern; 2000-2099; Exhibition catalogs; Ausstellungskatalog -- 14.09.2023-31.12.2023 -- Lyon